Antimicrobial Therapy in Pediatric Sepsis: What Is the Best Strategy? - Mau, Luciana Becker; Bain, Vera (Frontiers in Pediatrics, 2022)
Pediatric sepsis is a relevant cause of morbidity and mortality in this age group. Children are affected differently in high and low-income countries. Antibiotics are crucial for the treatment of sepsis, but indiscriminate use can increase resistance worldwide. The choice of a correct empiric therapy takes into consideration the site of infection, local epidemiology, host comorbidities and recent antibiotic exposure. Antibiotics should be administered in the first hour for patients with septic shock, and always intravenously or via intraosseous access. Culture results and clinical improvement will guide de-escalation and length of treatment. New diagnostic methods can help improve the prescription of adequate treatment. Prevention of sepsis includes vaccination and prevention of healthcare-associated infections. More research and education for awareness of sepsis is needed to improve care.